Detection of a potyvirus related to guineagrass mosaic virus infecting Brachiaria spp. in South America - Morales, Francisco José; Castaño, M.; Velasco, Ana Cecilia; Arroyave, José A. (Scientific Societies, 1994)
A filamentous virus approximately 775 nm long was isolated from variegated plants of the tropical forage grass Brachiaria spp. collected in Colombia and Brazil, South America. Ultrathin sections of symptomatic leaf tissue showed cylindrical inclusions (scrolls) in the cytoplasm of infected cells. The virus was transmitted mechanically to selected species of Brachiaria, Panicum, and Paspalum but not to maize, sorghum, or sugarcane. The virus was also transmitted from and to B. brizantha by the aphid Myzus persicae in a nonpersistent manner. The virus was not seedborne in Brachiaria spp. Purified virus preparations had an A260/280 ratio of 1.30 and exhibited capsid protein heterogeneity (Mr 41, 34, 32, and 30 kDa) as determined by SDS-PAGE. The virus was closely related serologically to guineagrass mosaic virus from Africa, distantly related to watermelon mosaic virus-2, and not related to maize dwarf mosaic, sorghum mosaic, and sugarcane mosaic viruses. Results of our Serological and pathogenicity tests suggest that the virus isolated from Brachiaria spp. is a strain of guineagrass mosaic potyvirus (GGMV). This would be the first report on the occurrence of GGMV in the Americas.